Phase Identification of Nano-Phase Materials using Convergent Beam Electron Diffraction (CBED) Technique - Gyeungho Kim; Jae-Pyoung Ahn (한국현미경학회, 2006)
Improvements are made to existing primitive cell volume measurement method to provide a real-timeanalysis capability for the phase analysis of nanocrystalline materials. Simplification is introduced in theprimitive cell volume calculation leading to fast and reliable method for nano-phase identification and isapplied to the phase analysis of Mo-Si-N nanocoating layer. In addition, comparison is made between real-timeand film measurements for their accuracy of calculated primitive cell volume values and factors governing theaccuracy of the method are determined. About 5% accuracy in primitive cell determination is obtained fromcamera length calibration and this technique is used to investigate the cell volume variation in WC-TiC core-shell microstructure. In addition to chemical compositional variation in core-shell type structure, primitive cellvolume variation reveals additional information on lattice coherency strain across the interface.